PENGARUH PULMONARY REHABILITATION PROGRAM TERHADAP PENINGKATAN KUALITAS HIDUP PASIEN PENYAKIT PARU OBSTRUKSI KRONIK DI INSTALASI RAWAT INAP ROYAL PRIMA MEDAN - Constan Zamili; Arieli Wau; Epi Laia; Ferdinandus Zagoto; Tiarnida Nababan (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2019)
Chronic obstruction pulmonary disease (COPD) is a health problem that currently exists worldwide. Pulmonary disease of chronic obstruction requires special attention, in patients of chronic obstruction of lung disease subjected to limited activity, physical and psychological disorders so that it will affect the quality of his life. One of the efforts that can be done to improve the quality of his life is the granting of Pulmonary Rehabilitation Program. The study aims to determine the influence of Pulmonary Rehabilitation Program on improving the quality of life of chronic obstruction lung disease in hospital inpatient installations of Royal Prima Medan. This research is pre-ecperimental research. The large sample is 10 people. Samples taken using accidental sampling technique are aksidental sampling (accidental). The instruments used are the Pulmonary Rehabilitation Program and the questionnaire sheet of life quality. The test used in the study uses the Wilcoxon test. The results of the statistical test in the study obtained p value 0.014 can be concluded there is a significant influence between the pulmonary rehabilitation of the program on improving the quality of life of chronic obstruction pulmonary disease patients. The advice of this research is expected for the hospital especially the nurse further increase the pulmonary rehabilitation of the program especially in patients with chronic obstruction of lung disease to improve the quality of life.